Kepemimpinan Perempuan Dalam Kajian Majelis Tarjih Muhammadiyah (Telaah Analisis Gender) - Wahid, Wawan Gunawan Abd (Sunan Kalijaga State Islamic University & The Asia Foundation, 2004)
Within the world of patriarchy, it is very important to examine the issue of the leadership of women. This very issue, which was latent within the Islamic tradition, reappears in line with the emerging awareness on the needs of women to gain wider roles in the public sphere. The issue of women leadership is responded by various individuals and institutions. Amongst the institutions concern with the issue is the Majelis Tarjih and the division of the Development of Islamic Thought of the Muhammadiyah, These institutions pay special attention to the issue of the leadership of women within the areas of mu 'amalah and 'ibadah, One proof of the appreciation of the Majelis Tarjih on this issue is their attempts to examine various religious issues within the frame of gender analysis.